Comparison of life cycle assessment of large-scale biogas projects with different raw materials in China - Sun, Jiazheng; Qu, Youpei; Lyu, Xiaoyi; Ding, Xinjie; Miao, Xinying; Kumar, Awashi Mukesh; Qu, Jingbo (International Journal of Agricultural and Biological Engineering, 2024)
The anaerobic digestion (AD) disposal of stover and cattle manure is of great significance to the development of low-carbon economy and green energy in China, but it will also have an impact on the environment, and the degree of influence isdifferent for various raw materials. In this study, life cycle assessment (LCA) methods were applied to analyze and compare theimpact of corn stovers biogas projects (CSBP) and dairy manure biogas projects (DMBP) on the environment during the wholeoperation stage. The results of inventory analysis were evaluated by ReCiPe2016 Hierarchy(H) mid-point (problem-oriented)and end-point (destruction-oriented) method, respectively. The results showed that the net energy efficiency of CSBP washigher (763.903 kW·h/FU) and the greenhouse gas (GHG) emission reduction of DMBP was more (5541.418 kg CO2-eq/FU).The anaerobic digestion (AD) units have the greatest environmental impacts, and human carcinogenic toxicity is the largestenvironmental impact category (1.16-1.43 PE). The key to reducing environmental impact is reducing the input of chemicalsubstances and the waste of electric energy. Both CSBP and DMBP have a favorable impact on ecosystem quality andresources, and CSBP is more beneficial to the environment (–10.297 Pt). Co-digestion is an important measure to reduce theenvironmental damage from biogas projects. These research results provide theoretical support for the selection of rawmaterials for large-scale biogas projects in China, provide technical basis for reducing the impact of actual operation on theenvironment, and promote the resource utilization of agricultural waste and carbon dioxide emission reduction andsequestration.Keywords: life cycle assessment, environmental impact assessment, large-scale biogas projects, bioenergy, carbon dioxideemission reductionDOI: 10.25165/j.ijabe.20241702.8898Citation: Sun J Z, Qu Y P, Lyu X Y, Ding X J, Miao X Y, Awasthi M K, et al. Comparison of life cycle assessment of large-scale biogas projects with different raw materials in China. Int J Agric & Biol Eng, 2024; 17(2): 268–279